Changes in structure, morphology and electrochemical properties of NiCl2–FeCl3–PdCl2–graphite intercalation compound affected by gaseous hydrogen reduction process. (1st July 2016) - Rozmanowski, T.; Krawczyk, P.
Highlights: Ternary NiCl2 –FeCl3 –PdCl2 –GIC with a mixture of stage-4, 5 was obtained. Chemical reduction of NiCl2 –FeCl3 –PdCl2 –GIC leads to exfoliation of the compound. Electrochemical activity of NiCl2 –FeCl3 –PdCl2 –GIC increases after reduction. Abstract: In the present work the influence of the reduction treatment of NiCl2 –FeCl3 –PdCl2 –graphite intercalation compound (NiCl2 –FeCl3 –PdCl2 –GIC) on the structural, morphological and electrochemical properties were examined. NiCl2 –FeCl3 –PdCl2 –GIC was prepared by molten salts method using a purified flaky graphite and anhydrous chlorides of Ni, Fe and Pd as reactants. The reduction process of NiCl2 –FeCl3 –PdCl2 –GIC was carried out using gaseous phase H2 /Ar mixture. The characterization of the crystalline structure and morphological properties of original as well as reduced GIC were studied by XRD and SEM techniques. The electrochemical properties of the investigated materials were examined in alkaline media by cyclic voltammetry method. The results of XRD and SEM analysis have showed that during reduction treatment the exfoliation of NiCl2 –FeCl3 –PdCl2 –GIC occurs. The degree of exfoliation depends on the applied temperature. Increase in reduction temperature results in enhancement of exfoliation degree. The electrochemical investigations revealed that electrochemical behaviour of the reduced compound is also influenced by the temperature of the reduction process.